Rigorous computations of dynamical quantities - Xiaolong Niu (2016)
This thesis is concerned with rigorous computation of dynamical quantities. In particular, we provide rigorous computation of diffusion coefficients for uniformly expanding maps of the interval. Moreover, we provide a rigorous computational scheme for linear response and we apply it in the case of uniformly expanding circle maps. Our results have been implemented successfully on a computer. Examples are included to illustrate the computer implementation.